APLIKASI DAN PELATIHAN MESIN PEMBERSIH BATOK KELAPA DI BANJAR MENASA DESA SINABUN, KECAMATAN SAWAN KABUPATEN BULELENG - Astawa, K.; Lokantara, I.P.; Wijaksana, H.; Sugita, I.K.G. (Buletin Udayana Mengabdi, 2018)
Coconut in Latin is called Cocos nucifera is a plant that is included in this type of palm tree with fruit that is large enough compared with other types of plants palm. In Bali coconut fruit is often used in the execution of religious ceremonies, especially Hindus. But this time coconut shells were initially considered as objects of garbage littering the environment changed to craft products that have high sales value, but to clean up existing fibers dibatok is difficult because it requires a lot of time but the result was not optimal and inefficient. On the other hand there are craftsmen who require a coconut shell that is clean with good quality and capacity that many .. Therefore we need a tool or machine that is able to overcome this problem, so that his work would be more effective and efficient and can increase income. Method of activities undertaken to achieve the objectives of this service activity is the first survey to Sinabun Village neighborhood. Further prepare a draft drawing tools and once materialized purifier coconut shell followed by testing tools. From the test results can be generated between the use of machine time efficiency compared to the conventional way is 10: 2 minutes to purge every single coconuts and quality of the results were also much better than the manual way.